Slaying the dragons that sabotage protection measures to feed on the ash of your plant. Issue 4 (28th May 2021) - Chastain‐Knight, Denise
Abstract: Dragons are legendary winged monsters that breathe fire and feed on ash. Or so we think. This is a tale of three dragons that have evolved to hide in plain sight and quietly feed on the underpinnings of protection layers, eroding the effectiveness of process safety mitigation measures. These dragons are mischievous and feed off process upsets, near misses, and accidents. The Invisible Dragon roams around the plant breaking devices and causing people to make mistakes that set off alarms and causes safety instrumented systems (SIS) trips to initiate. Its special joy is creating initiating events that were not considered in the design. Tiny and Giant Dragons specialize in defeating the SIS protection layers, so that all three dragons can feed on the ash of an accident. The Tiny Dragon baits SIS designers with devices having extremely low failure rate data causing the humans to believe safety instrumented functions (SIF) are more reliable than they actually are. The Giant Dragon works alongside the Tiny Dragon to further undermine the SIS with its song of near perfect proof testing. This paper will illustrate the impacts of underestimating SIF demand rate, using overly optimistic failure rate data, and overestimating proof test coverage. We will discuss techniques to identify and correct these issues and suggest metrics to monitor SIS performance thus slaying the dragons.